Intelligent Computer Systems in Engineering Design Principles and Applications - Sunnersjö, Staffan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This introductory book discusses how to plan and build useful, reliable, maintainable and cost efficient computer systems for automated engineering design. The book takes a user perspective and seeks to bridge the gap between texts on principles of computer science and the user manuals for commercial design automation software. The approach taken is top-down, following the path from definition of the design task and clarification of the relevant design knowledge to the development of an operational system well adapted for its purpose. This introductory text for the practicing engineer working in industry covers most vital aspects of planning such a system. Experiences from applications of automated design systems in practice are reviewed based on a large number of real, industrial cases. The principles behind the most popular methods in design automation are presented with sufficient rigour to give the user confidence in applying them on real industrial problems. This book is also suited for a half semester course at graduate level and has been complemented by suggestions for student assignments grown out of the lecture notes of two postgraduate courses given annually or biannually during the last ten years at the Product development program at the School of Engineering at Jönköping University. .
Introduction -- Industrial products and how they are developed -- Computerised methods to Design For Variety, DFV.-Clarifying, idealising and modelling of engineering knowledge -- Problem structure and knowledge processing -- Representation and processing of explicit knowledge -- Representation and processing of implicit knowledge -- Planning a Design Automation System -- Appendix 1: Industrial DA systems in production or prototyping -- Exercises.
Keywords: Engineering design; Computational intelligence; Computer-aided engineering; Artificial intelligence; Control engineering; Robotics; Automation; Engineering Design; Computational Intelligence; Computer-Aided Engineering (CAD, CAE) and Design; Artificial Intelligence; Control, Robotics, Automation